Hubungan antara Volume Prostat dengan Derajat International Prostate Symptoms Score (IPSS) pada Pasien Benign Prostatic Hyperplasia (BPH) dengan Lower Urinary Tract Symptoms di Poli Urologi RSUD Tabanan - Tri Krisnanda Pramarta; Komang Trisna Sumadewi; Ida Bagus Tatwa Yatindra (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
Benign Prostatic Hyperplasia (BPH) or benign prostate is a disease caused by swelling or an increase in the prostate gland. BPH occurs due to an increase in the volume of the prostate, the prostate is a solid organ located under the bladder, in front of the rectum and encloses the posterior urethra. One of the clinical manifestations of BPH is Lower Urinary Tract Symptoms (LUTS). To determine the degree of severity of these symptoms can be measured using the International Prostate Symptom Score (IPSS) questionnaire. This study aims to determine the relationship between prostate volume and the degree of IPSS in BPH patients with LUTS at the Urology Polyclinic of Tabanan Hospital. Sampling using consecutive sampling technique with the type of observational analytic research with cross-sectional techniques obtained as many as 40 respondents. The data obtained were analyzed univariately and bivariately using the gamma corelations test method with a 95% confidence level (p <0.05) using SPSS 25.0. The results obtained are as follows: there is a significant relationship between prostate volume and the degree of LUTS (p = 0.006) with the strength of the relationship in the strong category (r = 0.618). The conclusion is that prostate volume and IPSS degree have a significant relationship.